The nutritive value of four varieties of sorghum grain - McCollough, R.L.; Drake, C.L.; Harrison, K.F. (Kansas State University. Agricultural Experiment Station, 2011)
In 1969, Kansas harvested 182, 896, 00 bushels from 3,266,00 acres of grains sorghum for a 56-bushel-per-acre average. Much of it is fed to beef cattle; therefore, it would be an economic advantage for both grain producers and cattle feeders to have a sorghum grain of superior feeding quality.
Keywords: Beef; Sorghum grain; Feed quality; White sorghum grain